Antibacterial activity of Bixa orellana L. (achiote) against Streptococcus mutans and Streptococcus sanguinis - Medina Flores, Dyanne Adenea (2016)
Objective To evaluate the cytotoxic and antibacterial effect of Bixa orellana L. (B. orellana) (achiote) methanol extract against Streptococcus mutans (ATCC 25175) (S. mutans) and Streptococcus sanguinis (ATCC 10556) (S. sanguinis). Methods Two methanol extracts of B. orellana were prepared in vitro, from the seeds and leaves. The antibacterial activity of extracts against S. mutans and S. sanguinis was evaluated using the cup-plate agar diffusion method. The minimum inhibitory concentration (MIC) was determined using the microdilution method and the cytotoxic activity was determinated by using the cell line MDCK. Results A stronger antibacterial effect was observed with the leaves methanolic extract with an inhibition zone of (19.97 ± 1.31) mm against S. mutans and (19.97 ± 1.26) mm against S. sanguinis. The methanolic extract of the seeds had an activity of (15.11 ± 1.03) mm and (16.15 ± 2.15) mm against S. mutans and S. sanguinis, respectively. The MIC of the leaf and the seed extracts against S. sanguinis was 62.5 and 125 μg/mL, respectively, and the MIC of the leaf extract against S. mutans was 62.5 μg/mL, and for the seed extract it was 31.25 μg/mL. The 50% cytotoxic concentration was 366.45 and 325.05 μg/mL for the leaves and seeds extracts, respectively. Conclusions The experimental findings demonstrated the antibacterial effect of the methanolic extract of B. orellana (achiote) on S. mutans and S. sanguinis. The extract of this plant is cytotoxic at high concentrations.